Carbon-Free AZO/Ru Cathode for Li-Air Batteries. (1st January 2015) - Wu, Mihye; Suk, Jungdon; Jo, Ju Young; Kim, Yeon; Choi, Sungho; Kim, Dong Wook; Kang, Yongku; Jung, Ha-Kyun
Abstract : The aluminum-doped ZnO/Ru composite (AZO/Ru) was developed as a carbon-free cathode material for Li-air batteries for the first time. The AZO was synthesized by the fast and convenient microwave-assisted hydrothermal method and Ru was added as a catalyst to improve the electrochemical performance of the AZO/Ru. Adjusting the synthesis conditions can produce enhanced surface properties which affect the electrochemical properties of the AZO/Ru. Experimental results confirmed that formation of Li2 CO3 can be suppressed by an AZO/Ru cathode and established its applicability as a potential cathode material for Li-air batteries.